Designing A Geographic Information System Website For Tourism In Sukabumi Regency Using The Design Thinking Method - Rival Maulana; Sudin Saepudin; Gina Syabani Yuda (International Journal of Health Engineering and Technology, 2026)
The rapid development of digital technology has transformed the dissemination of tourism information, including weh-based tourim services. However, tourism information in Sukabumi Regency remains fragmented, with limited integration, an unattractive interface, and insufficient digital promotional media. This study aims to design the User Interface (UI) and User Experience (UX) of the Sukabumi Regency Tourism Geographic Information System (GIS) website using the Design Thinking method. The Design Thinking approach was selected because it emphasizes user needs through five stages: empathize, define, ideate, prototype, and test. Data were collected through interviews and observations involving tourists, administrators, and tourism managers to identify user needs and existing problems. The findings were analyzed using a User Journey Map and How Might We (HMW) framework to define design opportunities. Design solutions were then developed through mind maps, user flows, wireframes, and UI fundamentals, followed by the creation of an interactive prototype using Figma. The prototype was evaluated using the System Usability Scale (SUS) with fifteen respondents representing the three user groups. The evaluation produced an average SUS score of 69.8, which falls into Grade B, with a “Good” adjective rating and an “Acceptable” usability range. These findings indicate that the proposed website provides satisfactory usability, is easy to use, and effectively meets user needs.